HnRNPU regulates intra- and intercellular microRNA trafficking in a sequence specific manner. (25th November 2020) - Zietzer, A; Hosen, M.R; Goody, P.R; Werner, N; Nickenig, G; Jansen, F
Abstract: Introduction: The transfer of microRNAs (miRs) through extracellular vesicles (EVs) is a well-established mechanism of vascular intercellular communication. In a previous study, we have identified the heterogeneous nuclear ribonucleoprotein U (hnRNPU) as a potent regulator of the vesicular export of a specific set of miRs in endothelial cells (ECs). Downregulation of hnRNPU caused an increased export of miRs into large EVs and lead to a reduction of the migratory capacity in EV up-taking ECs. The underlying mechanism, how hnRNPU recognizes only certain miRs and regulates their export, however, remained unclear. Methods and results: Increasingly exported microRNAs into EVs after siRNA-mediated downregulation of hnRNPU were identified in a miR array and used to perform a sequence analysis with the Multiple Em for Motif Elicitation tool (MEME). The software identified the motif AAMRUGCU to be significantly enriched within the regulated miRs. Binding of hnRNPU to miR-30c-5p, which was one of the most significantly increased miRs in EVs upon downregulation of hnRNPU, was confirmed in an immunoprecipitation and an RNA-pulldown experiment. In order to investigate, if the in silico motif AARUGCU was the binding site of miR-30c-5p and hnRNPU an electrophoretic mobility shift assay (EMSA) was conducted with native miR-30c-5p, mutated miR-30c-5p as well as miR-125a-3p as a negative control. The EMSA showed that a partial mutation, which conserves the purine / pyrimidine structure in the motif of miR-30c-5p does not affect binding, while a complete disruption of the motif structure abolishes binding of hnRNPU and miR-30c-5p. Furthermore, we found that hnRNPU protects miR-30c-5p from rapid degradation after transcriptional blockage by Actinomycin D. Binding of miR-30c-5p to the predominantly nuclearly expressed hnRNPU retains miR-30c-5p in the nucleus. HnRNPU knockdown leads to a redistribution of miR-30c-5p from the nucleus to the cytoplasm. The regulating effect of hnRNPU expression on vesicular miR export was confirmed by overexpression of hnRNPU through plasmid transfection. In contrast to siRNA-mediated downregulation, overexpression of hnRNPU lead to a decrease of vesicular miR-30c-5p levels. In order to extent our findings to other cell types with high vascular relevance, siRNA mediated downregulation of hnRNPU was performed in human cardiac fibroblasts (HCF). Similar to our findings in ECs, downregulation of hnRNPU in HCFs lead to an increase in vesicular miR-30c-5p levels. Conclusion: In conclusion, we show that hnRNPU binds miRs, which contain the motif AAMRUGCU. This leads to nuclear retainment, stabilization and inhibits vesicular export, which can be further decreased by overexpression of hnRNPU and enhanced by downregulation of hnRNPU. The effect is not restricted to ECs but applies also to HCFs. hnRNPU may therefore be an important target to influence intra- and intercellular trafficking of a specific set of miRs including miR-30c-5p. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Medical faculty of the University of Bonn, German Cardiac Society